Using experts’ consensus to evaluate the Readiness Factors of Lean Implementation in Healthcare (International Journal of Scientific Research and Management (IJSRM), 2022)
BACKGROUND: The core idea of the Lean philosophy in healthcare is a continuous improvement by minimizing waste and maximizing the value delivered to patients. Although there is growing interest in lean applications in healthcare organizations, the study of readiness factors for implementing Lean in this sector remains one of the reasons for Lean failure. OBJECTIVE: This study aims to identify and validate the readiness factors that influence the successful and sustainable implementation of Lean in healthcare organizations. METHODS: A systematic review of the literature was performed to synthesize readiness factors that help healthcare organizations implement lean practices. The Delphi method was used to validate the identified factors from the perspective of the healthcare experts. RESULTS: This systematic review revealed eleven readiness factors that are important contributors to the success of Lean implementation in healthcare. After three rounds of Delphi, a moderate consensus (Kendall’s W=0.519; P<0.001) was achieved among the experts’ panel regarding the nine readiness factors. Seven factors were extracted from the literature review and two were derived from experts’ suggestions. CONCLUSIONS: The investigation of organizational readiness to implement lean may help healthcare organizations be better prepared for their initiation of the Lean journey and enable the sustainability of improvements.